PERAN PEREMPUAN PANDULUNG DALAM PEMBERDAYAAN EKONOMI PESISIR DI UJUNG LERO KABUPATEN PINRANG - Mardiyah Mardiyah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper would like to publish the results of Partisipation Action Research-based service about Pandulung Women's Fishermen Community in Ujung Lero is a picture of people's lives that are marginal, marginalized, poor, helpless and unempowered. Their everyday life is colored by just wrestling with fish on the coast of Ujung Lero. The community of fishermen women makes the work of Pandulung as the main focus of family life. This community is interesting to be empowered and researched, because it has good potential, interests, and opportunities for the future. However, the great interest and opportunity to change from the economic downturn has not been matched by adequate knowledge and understanding. Therefore, as a recommendation, the involvement of various stakeholders in depth is needed to raise the problem of economic downturn towards better economic independence.